An Approach on Building Envelope-Isolation from Water Reinforcements and Their Sustainability in Traditional Residential Architecture - Akat, Reyhan; Çakıroğlu, Birgül (Technium Social Sciences Journal, 2024)
Roof and roofings built to protect the housing and homeowner from undesirable rainwater, have been seen an important structural element throughout history in the entire of housing. In this research, structural and spatial relationships between building envelope with isolation from water in traditional housing architecture are analyzed. Roof, eaves and rain gutters which are isolation from water items were investigated according to shapes, slope direction, materials, carrier systems and covering materials. The qualification of the roofing, eave and rain gutter elements which are equipment elements related to the comfort of the building envelope and the extent of changes in these elements were examined at the traditional housing level. Exemplary, the traditional housing in the city of Trabzon in Turkey were selected. During the completion process of the working, detailed aims related to structure-health reinforcements were specified with the relevant literature review. The chart form has been developed for compilation of information about the general characteristics of the housing in the research area and the building-health reinforcements within the aim of the research. Exemplary houses were selected by external observation technique and the data obtained as a result of observations, interview and determinations related to general characteristics and building-health reinforcements of these housing were handled into a chart form. By evaluating the data obtained; harmony and contrasts in system level practices, the dimensional properties of the elements at the spatial level, the greatness and accuracy levels preferred in various fittings, the harmony and contrasts in the materials, dimensions and practices of the elements at the system and spatial level, harmony and contrasts of applications of new opportunities at the level of building-health reinforcements in traditional housing, conclusions were drawn to identify special and general situations at the level of building-health reinforcements and to obtain information about the comfort requirements of traditional housing. Nowadays, where the health of the building, which is mostly ignored, is gaining importance day by day, concrete and applicable solution data are presented and interpreted for new designs to be made in this direction.